Influence of Contextual Factors, Technical Performance, and Movement Demands on the Subjective Task Load Associated With Professional Rugby League Match-Play - Mullen, T.; Twist, C.; Daniels, M.; Dobbin, N.; Highton, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To identify the association between several contextual match factors, technical performance, and external movement demands on the subjective task load of elite rugby league players.